Refugee flows, foreign policy, and safe haven nexus in Turkey - Oztig, Lacin Idil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
While the relationship between refugees and foreign policy has been extensively studied, scarce attention has been paid to the linkages between refugee flows and safe haven policy as foreign policy. This article fills this gap in the literature by comparatively examining Turkey's refugee and safe haven policies. Turkey witnessed two major influxes of refugees: after the Saddam Hussein regime oppressed the Kurdish uprising in 1991 and following the outbreak of the Syrian civil war in 2011. Turkey closed its Iraqi border to the Kurdish refugees and labelled their mass movement as a threat to its national security. In sharp contrast, Turkey has generally adopted accommodative policies towards Syrian refugees with a strong emphasis placed on humanitarian values. During both crises, Turkey supported safe haven policies for the repatriation of refugees to their home countries on international platforms. While Turkey was immediately able to persuade the international community for the creation of a safe haven in northern Iraq, it was less successful with respect to northern Syria, as it could only put its safe haven project on the negotiation table after relying more heavily on brute force.
Keywords: Refugee flows; safe haven policy; foreign policy; Turkey; Iraq; Syria; FORCED MIGRATION; RESPONSES; Development Studies